2017
DOI: 10.5796/electrochemistry.85.559
|View full text |Cite
|
Sign up to set email alerts
|

Developing New Functionalities of Superconcentrated Electrolytes for Lithium-ion Batteries

Abstract: The nature of electrolyte solutions is dominated by the three factors of Li salts, solvents, and their mixing ratios (salt concentrations). Conventionally, the selections of Li salts and solvents have been considered of prime importance for Li-ion battery electrolytes, while the salt concentrations have been always fixed to approximately 1 mol dm −3 based on maximized ionic conductivities. Recently, however, the salt concentrations are increasingly recognized as a key to developing new functionalities for batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Combining ARC and DSC technique, the author concluded that the two cells fail for the oxidation of electrolyte and the formation of LiF, respectively. While as reported in many previous reports, LiF is an important component in the SEI (Wu et al, 2012;Yamada, 2017), moreover, SEI regeneration was also mentioned in several papers (Feng et al, 2018b), therefore, we consider that it is the crosstalk between cathode and anode which influenced the stability of SEI and further lead to this special phenomenon.…”
Section: Cathode Materialsmentioning
confidence: 48%
“…Combining ARC and DSC technique, the author concluded that the two cells fail for the oxidation of electrolyte and the formation of LiF, respectively. While as reported in many previous reports, LiF is an important component in the SEI (Wu et al, 2012;Yamada, 2017), moreover, SEI regeneration was also mentioned in several papers (Feng et al, 2018b), therefore, we consider that it is the crosstalk between cathode and anode which influenced the stability of SEI and further lead to this special phenomenon.…”
Section: Cathode Materialsmentioning
confidence: 48%
“…6 Recently, a novel concept for practical LIB electrolyte materials with highvoltage operation has been proposed, i.e., super-concentrated electrolytes. [7][8][9][10][11] This concept has been widely investigated, not only in the field of LIB chemistry/technology, but also for fundamental science at the molecular level (structure and dynamics in the liquid state), both experimentally and theoretically. [12][13][14][15][16][17] Highly concentrated electrolytes can be successfully applied to both non-aqueous [18][19][20][21][22] and aqueous [23][24][25][26] solution systems to enable reversible, stable, and working LIBs with adequate electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using highly concentrated electrolytes for battery applications have been demonstrated not only with ionic liquids but also with many common organic molecular solvents (also known as superconcentrated solvent-based electrolytes or solvent-in-salt electrolyte), which includes organic carbonates, sulfoxides, ethers, nitriles, and so on. [27][28][29][30][31] The differences between highly concentrated solvent-based and ILbased systems largely come from the choice of solvent. From a simulation point of view, different solvents lead to different alkali metal ion coordination geometries.…”
Section: Introductionmentioning
confidence: 99%